Nutrient Solution Deprivation as a Tool to Improve Hydroponics Sustainability: Yield, Physiological, and Qualitative Response of Lettuce - Ciriello, Michele; Formisano, Luigi; Pannico, Antonio; El-Nakhel, Christophe; Fascella, Giancarlo; Duri, Luigi Giuseppe; Cristofano, Francesco; Gentile, Beniamino Riccardo; Giordano, Maria; Rouphael, Youssef; Fusco, Giovanna Marta; Woodrow, Pasqualina; et al. (Agronomy (Basel), 2021)
Hydroponics growing systems often contain excessive nutrients (especially nitrates), which could lead to a quality loss in ready-to-eat leafy vegetables and posing a health risk to consumers, if managed inadequately. A floating raft system was adopted to assay the production and quality performance of lettuce (Lactuca sativa L. cv ‘Maravilla De Verano Canasta’) deprived of the nutrient solution by replacement with only water, three and six days before harvest. Yield and quality parameters, mineral composition, pigments, organic acids, amino acids profile, soluble proteins, and carbohydrate content were determined. Nutrient solution deprivation six days before harvest resulted in a significant reduction in leaf nitrate (−53.3%) concomitant with 13.8% of yield loss, while plants deprived of nutrient solution three days before harvest increased total phenols content (32.5%) and total ascorbic acid (102.1%), antioxidant activity (82.7%), anthocyanins (7.9%), sucrose (38.9%), starch (19.5%), and γ-aminobutyric acid (GABA; 28.2%), with a yield reduction of 4.7%, compared to the control. Our results suggest that nutrient solution deprivation three days before harvest is a successful strategy to reduce nitrate content and increase the nutritional quality of lettuce grown in floating raft systems with negligible impact on yield. These promising results warrant further investigation of the potential effect of nutrient solution deprivation on the quality attributes of other leafy vegetables cultivated in floating raft systems and in a “cascade” growing system.